Proyecto de factibilidad para la implantación de una microempresa productora de pulpa de arazá y su comercialización en la provincia de Sucumbios. - Escobar Acaro, Rosa Verónica (2012)
The present work corresponds to a study of feasibility dedicated to determine the convenience of implementing a company for the production and commercialization of arazá pulp in the County of Sucumbíos. The study begins with a situational analysis in which is included diverse categories that allow to understand the managerial idea, that is to say the production of arazá pulp. Immediately the project contemplates a market study in which the conditions of the offer and the demand are determined, the same one that estimates a total of unsatisfied demand of 1.264.715 units of 500 gr. of arazá pulp. The technical study allowed to establish the good size of the project, the unsatisfied demand of this product shows that it is viable the implementation of this company type, with a capacity installed to produce 211.200 units of 500gr. of arazá pulp a year, being used 100% of the installed capacity, during the 10 years of life of the project, the same one that will have a participation of 16.70% of the unsatisfied demand. The company "PULP DE ARAZA CIA LTDA "in the County of Sucumbíos, he/she has an organizational structure that completes a fundamental paper in the execution of the project, therefore it is important to emphasize the participation of necessary people for administration, for the operative area and of sales The total of active fixed it is of 18.428.55 dollars, Assets Differed 2.730 dollars, Capital of Operation 16.545.19 dollars, giving a total of Investment of 37.703.74 dollars; He/she will conform to a company of limited responsibility that will have three partners, which will finance, the credit with the Bank of Development that will constitute 50% that corresponds to 18.851.87 dollars to 10 years term to 11% of annual interest. The State of Results sample a net utility of 32867, 14 in the first period and successively he/she will go increasing he/she stops the following years. In the evaluation of the project it was evidenced that the net current value (they GO) it is positive with a value of 182.358,67; the internal rate of return (TIR) it is of 90,47%; the relationship of the benefit cost indicates that for each invested dollar it will be obtained 0.25 cents of yield; the investment will recover in 1 year, 3 months and 14 days; and, based on the analysis of the sensibility a satisfactory result is demonstrated that allows 16,92 increment% in the costs and a decrease in the revenues of 13,55%. Consequentlythefeasibility of theproject has beendemonstrated. When the values of sen owning improv are lower than 1, therefore does not affect the draft changes in revenues and costs disminuidos or plus a 16.92 % and in a 13.55 %, respectively; that is to say, the project is not sensitive to these changes as was demonstrated when calculating the other indexes.